Surgery Induces Cyclooxygenase-2 Expression in the Rat Cervical Spinal Cord. Issue 6 (1st October 2009) - Brennan, Louise K.; Harte, Brian H.; Fitzgerald, Desmond J.; McCrory, Connail R.
Abstract : Background and Objectives: Nonsteroidal anti-inflammatory drugs with a selective cyclooxygenase-2 (COX-2) inhibitory profile are effective analgesics in the postoperative period. This implies that surgery induces COX-2 biosynthesis. We examined whether peripheral surgical trauma can induce COX-2 expression in the rat cervical spinal cord. Methods: Sprague-Dawley rats were divided into 2 groups. The control group underwent general anesthesia but had no surgery. The surgical group underwent general anesthesia and surgical exposure of neck structures. After 14 days, the animals were euthanized, and a section of cervical spinal cord was taken to identify COX-1 and COX-2 expression by immunohistochemical analysis. Two independent blinded observers analyzed the slides. Results: Analysis of COX-1 protein expression revealed homogenous staining in glial cells in all regions of the cervical spinal cord examined. There was no difference in expression between the control and surgical groups. However, whereas the control group demonstrated minimal COX-2 expression, the surgical group showed extensive neuronal and glial cell cytoplasmic COX-2 expression. Conclusions: This study demonstrates that surgery induces COX-2 expression in the rat cervical spinal cord. This could provide a scientific rationale for the use of selective COX-2 inhibitors as analgesics in the postoperative period.